Bis(tercarbazole) pyrene and tetrahydropyrene derivatives: photophysical and electrochemical properties, theoretical modeling, and OLEDs. Issue 17 (8th April 2019) - Kaafarani, Bilal R.; El-Assaad, Tarek H.; Smith, William A.; Ryno, Sean M.; Hermerschmidt, Felix; Lyons, Jeffrey; Patra, Digambara; Wex, Brigitte; List-Kratochvil, Emil J. W.; Risko, Chad; Barlow, Stephen; Marder, Seth R.
Abstract : The title compounds are compared to bis(carbazole) analogues. They exhibit multiple oxidations, dual fluorescence (in one case), and function as emissive layers in OLEDs. Abstract : 2, 7-Bis(3, 3′′, 6, 6′′-tetra( tert -butyl)-9′ H -9, 3′:6′, 9′′-tercarbazol-9-yl)-4, 5, 9, 10-tetrahydropyrene (3 ) and 2, 7-bis(3, 3′′, 6, 6′′-tetra( tert -butyl)-9′ H -9, 3′:6′, 9′′-tercarbazol-9-yl)pyrene (4 ), along with a model compound, 3, 3′′, 6, 6′′-tetra( tert -butyl)-9′-(4-( tert -butyl)phenyl)-9′ H -9, 3′:6′, 9′′-tercarbazole (6 ), have been synthesized using microwave-assisted palladium-catalyzed coupling and compared to analogous 3, 6-di( tert -butyl)carbazol-9-yl species (1, 2, and 5 ). Time-dependent density functional theory (TDDFT) calculations reveal absorption with quadrupolar (ter)carbazole-to-bridge CT character for 1–4 . Compound 4 is unusual in showing dual fluorescence in a number of solvents; the longer wavelength feature of which is markedly more solvatochromic than the bands of the other compounds. Following the observed three oxidations on the TCz model compound 6, compounds 3 and 4 can be electrochemically reversibly oxidized to hexacations with four oxidation and three oxidation steps in a 2 : 2 : 1 : 1 and a 2 : 2 : 2 current ratio, respectively. Tercarbazole derivatives 3 and 4 have been used as the emissive layers of simple solution-processed few-layer organic light-emitting diodes.